2020
DOI: 10.1142/s0192415x20500299
|View full text |Cite
|
Sign up to set email alerts
|

Corosolic Acid Attenuates Hepatic Lipid Accumulation and Inflammatory Response via AMPK/SREBPs and NF-κB/MAPK Signaling Pathways

Abstract: Corosolic acid (CA) is the main active component of Lagetstroemia speciosa and has been known to serve as several different pharmacological effects, such as antidiabetic, anti-oxidant, and anticancer effects. In this study, effects of CA on the hepatic lipid accumulation were examined using HepG2 cells and tyloxapol (TY)-induced hyperlipidemia ICR mice. CA significantly inhibited hepatic lipid accumulation via inhibition of SREBPs, and its target genes FAS, SCD1, and HMGCR transcription in HepG2 cells. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In this study, we found that 48 h treatment of 20 μM nuciferine could significantly promote the mRNA and protein levels of FGF21 in the fully differentiated adipocytes, suggesting that the inhibitory effect of nuciferine on lipogenesis in adipocytes may also achieved through promoting the beneficial adipokine FGF21 expression in addition to its direct inhibitory effect of the expression of key lipogenesis enzymes in 3T3-L1 adipocytes. One possible explanation for this phenomenon is based on studies conducted by Salminen A et al who showed that FGF21 could activate AMPK pathway (Salminen et al, 2017), while (Zhang et al, 2020) found that activation of AMPK pathway could inhibit the expression of SREBP1, FAS and ACC. Therefore, we raised a presumption that nuciferine may promoted the expression of FGF21 and subsequently activate intracellular AMPK pathway, thus inhibiting the expression of enzymes related to fat synthesis and reducing intracellular fat contents in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that 48 h treatment of 20 μM nuciferine could significantly promote the mRNA and protein levels of FGF21 in the fully differentiated adipocytes, suggesting that the inhibitory effect of nuciferine on lipogenesis in adipocytes may also achieved through promoting the beneficial adipokine FGF21 expression in addition to its direct inhibitory effect of the expression of key lipogenesis enzymes in 3T3-L1 adipocytes. One possible explanation for this phenomenon is based on studies conducted by Salminen A et al who showed that FGF21 could activate AMPK pathway (Salminen et al, 2017), while (Zhang et al, 2020) found that activation of AMPK pathway could inhibit the expression of SREBP1, FAS and ACC. Therefore, we raised a presumption that nuciferine may promoted the expression of FGF21 and subsequently activate intracellular AMPK pathway, thus inhibiting the expression of enzymes related to fat synthesis and reducing intracellular fat contents in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CA could possess hepatoprotective effect in CCl 4 -induced liver toxicity in rats (Balakrishnan & Al-Assaf, 2016). Our laboratory has confirmed that CA has hepatic protective effects against tyloxapol-induced ICR mice liver injury (Zhang et al, 2020). However, there are no studies on the treatment of steatohepatitis with CA.…”
mentioning
confidence: 75%
“…In this study, CA effectively reduced the levels of TG, TC, ALT, AST, and LDL-C in the serum of hyperlipidemic mice, whereas the level of HDL-C showed an increasing trend. 100 In conclusion, HE can play a significant role in lipid regulation, mainly involving the improvement in the levels of LDL, HDL, AST, ALT, TG, TC, and other lipid markers, but the specific mechanism is unclear. Hence, further studies are needed to explore the mechanism of HE in lipid regulation.…”
Section: Reviewmentioning
confidence: 96%
“…In this study, CA effectively reduced the levels of TG, TC, ALT, AST, and LDL-C in the serum of hyperlipidemic mice, whereas the level of HDL-C showed an increasing trend. 100…”
Section: Vascular Protective Effects Of He In Cvdmentioning
confidence: 99%